Phenolic content and antioxidant activity of the Croatian red clover germplasm collection - Horvat, Daniela (Array, 2020)
The leaf samples of two varieties, twenty breeding populations, and seven local populations of the Croatian red clover were collected in the full flowering stage, with an aim to evaluate their phenolic content and antioxidant activity by using the spectrophotometric methods. A significant variation among the varieties/populations in the content of total phenolics and flavonoids was determined. The results demonstrated that the red clover is a rich source of phenolics and flavonoids, ranging from 38.67 to 59.96 mg GAE/g of DM and 21.19 to 51.48 mg CE/g of DM, respectively. The high levels in both phenolics and flavonoids were found in breeding populations/variety CD-8, Rc-11/7, Rc-11/8, Rc-11/15 and OS Osiris. The leaf extracts manifested a strong antioxidant activity towards diphenyl-1-picrylhydrazyl (DPPH), with a variation from 31.50 to 63.14%. A significant correlation was found between the antioxidant activity of the extracts and their total phenolic and flavonoid content (r = 0.737 and 0.839, respectively). Considering the obtained results, the crude extracts of red clover manifested a significant antioxidant potential and can be used as a natural source of biologically active components in the human and animal nutrition.